Luqman's advice to his son: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story shares the wise counsel of Luqman, who imparts valuable life lessons to his son about faith, gratitude, and morality. It emphasizes the importance of wisdom, respect for parents, and the need to seek knowledge, encouraging young readers to embrace these teachings in their own lives.